Immunotherapeutic Targets in Liver Diseases: A Literature Review - Evelina, Felya (Jurnal Biologi Tropis, 2025)
Liver diseases, including alcoholic liver disease (ALD) and non-alcoholic fatty liver disease (NAFLD), are major global health problems associated with high morbidity and mortality. Both conditions share overlapping immunopathogenic mechanisms characterized by hepatocyte injury, oxidative stress, and chronic inflammation driven by innate and adaptive immune activation. This review aims to summarize recent advances in identifying immunotherapeutic targets for ALD and NAFLD. Key immune pathways involved include activation of Kupffer cells, neutrophil infiltration, and cytokine release (such as TNF-α, IL-1β, and IL-6), which promote hepatocellular damage and fibrosis. Emerging therapeutic strategies focus on inhibiting inflammasomes, modulating Toll-like receptor 4 (TLR4) signaling, targeting chemokine receptors (CCR2/CCR5), enhancing IL-22-mediated regeneration, and restoring gut-liver axis balance through probiotics or fecal microbiota transplantation. Furthermore, agents acting on metabolic immune cross talk, such as PPAR and FXR agonists, have shown promising outcomes in preclinical and clinical studies. Overall, immunotherapeutic approaches offer a promising avenue for mitigating liver inflammation and fibrosis. Continued exploration of these targets may lead to effective, individualized therapies for chronic liver disease.